2000
DOI: 10.1161/01.str.31.12.3029
|View full text |Cite
|
Sign up to set email alerts
|

Stent Angioplasty for Cervical Carotid Artery Stenosis in High-Risk Symptomatic NASCET-Ineligible Patients

Abstract: Background and Purpose —Although the North American Symptomatic Carotid Endarterectomy Trial (NASCET) has shown carotid endarterectomy (CEA) to be protective compared with medical therapy alone, its stringent eligibility criteria excluded patients with severe medical, angiographic, and neurological risk factors. We sought to determine the safety and efficacy of stent angioplasty in this high-risk subset for whom the perioperative morbidity and mortality of surgery are elevated. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0
6

Year Published

2001
2001
2014
2014

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 84 publications
(37 citation statements)
references
References 31 publications
1
30
0
6
Order By: Relevance
“…This excludes the other studies that represented very-high-risk cohorts. 98,99,[102][103][104][105] Similar favorable results were reported by Al-Mubarak et al, who reported on 51 consecutive patients undergoing simultaneous or staged carotid artery stenting and percutaneous coronary intervention. Technical success was achieved in all carotid arteries, with a minor stroke rate of 4% and no major strokes, myocardial infarctions, or deaths.…”
Section: Carotid Stentingsupporting
confidence: 57%
“…This excludes the other studies that represented very-high-risk cohorts. 98,99,[102][103][104][105] Similar favorable results were reported by Al-Mubarak et al, who reported on 51 consecutive patients undergoing simultaneous or staged carotid artery stenting and percutaneous coronary intervention. Technical success was achieved in all carotid arteries, with a minor stroke rate of 4% and no major strokes, myocardial infarctions, or deaths.…”
Section: Carotid Stentingsupporting
confidence: 57%
“…Surgical endarterectomy has been shown to be superior to medical treatment in severe stenosis, but carries a substantial peri-procedural death and stroke rate of 2–7% even in highly selected patients [1, 2, 3]. Transcatheter endovascular stenting may be a safe and effective alternative to endarterectomy [4], especially in patients at high surgical risk [5, 6]. In Taiwan, the incidence of carotid stenosis in patients with cortical infarction is reported to be 32% [7], and hereafter we report our series of consecutive endovascular carotid interventions in this pure ethnic Chinese population.…”
Section: Introductionmentioning
confidence: 99%
“…While the heterogeneity of patient populations might hamper the comparability of data across various institutions, we classified patients with respect to their surgical risk on the basis of an established scoring system [12]. Since both surgical and non-surgical groups contained patients with multiple comorbid conditions and elevated periprocedural risks (modified Sundt grades 3–4) and no significant differences between the complication rates in these groups were found the common practice of preferentially submitting high-risk patients to CAS might not be justified [18, 19, 20]. In the group of surgical patients there were no instances of myocardial infarction or respiratory complications, suggesting that surgical patients do not have a higher rate of non-neurological complications than might be expected when undergoing anesthesia for a major operation.…”
Section: Discussionmentioning
confidence: 99%